BMS-871: A novel orally active pan-Notch inhibitor as an anticancer agent. Issue 9 (1st May 2015) - Shan, Weifang; Balog, Aaron; Quesnelle, Claude; Gill, Patrice; Han, Wen-Ching; Norris, Derek; Mandal, Sunilkumar; Thiruvenkadam, Raja; Gona, Kiran Babu; Thiyagarajan, Kamalraj; Kandula, Sathiah; McGlinchey, Kelly; et al.
Graphical abstract